Finding the Fuse: Prospects for the Detection and Characterization of Hydrogen-rich Core-collapse Supernova Precursor Emission with the LSST - A. Gagliano; E. Berger; V. A. Villar; D. Hiramatsu; R. Kessler; T. Matsumoto; A. Gilkis; E. Laplace (The Astrophysical Journal)
Enhanced emission in the months to years preceding explosion has been detected for several core-collapse supernovae (SNe). Though the physical mechanisms driving the emission remain hotly debated, the light curves of detected events show long-lived (≥50 days), plateau-like behavior, suggesting hydrogen recombination may significantly contribute to the total energy budget. The Vera C. Rubin Observatory’s Legacy Survey of Space and Time (LSST) will provide a decade-long photometric baseline to search for this emission, both in binned pre-explosion observations after an SN is detected and in single-visit observations prior to the SN explosion. In anticipation of these searches, we simulate a range of eruptive precursor models to core-collapse SNe and forecast the discovery rates of these phenomena in LSST data. We find a detection rate of ∼40–130 yr ^−1 for SN IIP/IIL precursors and ∼110 yr ^−1 for SN IIn precursors in single-epoch photometry. Considering the first three years of observations with the effects of rolling and observing triplets included, this number grows to a total of 150–400 in binned photometry, with the highest number recovered when binning in 100 day bins for 2020tlf-like precursors and in 20 day bins for other recombination-driven models from the literature. We quantify the impact of using templates contaminated by residual light (from either long-lived or separate precursor emission) on these detection rates, and explore strategies for estimating baseline flux to mitigate these issues. Spectroscopic follow-up of the eruptions preceding core-collapse SNe and detected with LSST will offer important clues to the underlying drivers of terminal-stage mass loss in massive stars.